Curative therapies are superior to standard of care (transarterial chemoembolization) for intermediate stage hepatocellular carcinoma. (2nd October 2016) - Pecorelli, Anna; Lenzi, Barbara; Gramenzi, Annagiulia; Garuti, Francesca; Farinati, Fabio; Giannini, Edoardo G.; Ciccarese, Francesca; Piscaglia, Fabio; Rapaccini, Gian Lodovico; Di Marco, Maria; Caturelli, Eugenio; Zoli, Marco; et al.
Abstract: Background & Aims: The Barcelona Clinic Liver Cancer intermediate stage (BCLC‐B) of hepatocellular carcinoma (HCC) includes extremely heterogeneous patients in terms of tumour burden and liver function. Transarterial‐chemoembolization (TACE) is the first‐line treatment for these patients although it may be risky/useless for someone, while others could undergo curative treatments. This study assesses the treatment type performed in a large cohort of BCLC‐B patients and its outcome. Methods: Retrospective analysis of 485 consecutive BCLC‐B patients from the ITA.LI.CA database diagnosed with naïve HCC after 1999. Patients were stratified by treatment. Results: 29 patients (6%) were lost to follow‐up before receiving treatment. Treatment distribution was: TACE (233, 51.1%), curative treatments (145 patients, 31.8%), sorafenib (18, 3.9%), other (39, 8.5%), best supportive care (BSC) (21, 4.6%). Median survival (95% CI) was 45 months (37.4–52.7) for curative treatments, 30 (24.7–35.3) for TACE, 14 (10.5–17.5) for sorafenib, 14 (5.2–22.7) for other treatments and 10 (6.0–14.2) for BSC ( P <.0001). Independent prognosticators were gender and treatment. Curative treatments reduced mortality (HR 0.197, 95%CI: 0.098–0.395) more than TACE (HR 0.408, 95%CI: 0.211–0.789) ( P <.0001) as compared with BSC. Propensity score matching confirmed the superiority of curative therapies over TACE. Conclusions: In everyday practice TACE represents the first‐line therapy in an half of patients with naïve BCLC‐B HCC since treatment choice is driven not only by liver function and nodule characteristics, but also by contraindications to procedures, comorbidities, age and patient opinion. The treatment type is an independent prognostic factor in BCLC‐B patients and curative options offer the best outcome.